THE CORRELATION BETWEEN VOCABULARY MASTERY AND ANALYTICAL EXPOSITION TEXT WRITING ABILITY OF THE TWELFTH-GRADE STUDENTS OF SMA NEGERI 1 GIANYAR IN ACADEMIC YEAR 2021/2022 - Kadek Indira Savitri; Ni Made Wersi Murtini; I Gde Putu Agus Pramerta (Journal on Studies in English Language Teaching (JOSELT), 2022)
The present study is a correlational study which its objective is to find out the correlation between twelfth-grade students’ vocabulary mastery and their writing ability in analytical exposition text. Population of the study is the twelfth-grade students of SMA Negeri 1 Gianyar in academic year 2021/2022. There are 72 students of the population that have been chosen as the sample of the present study by applying random sampling method which involved lottery system. Multiple cloze test items are used to obtain the data of vocabulary mastery while the data of the students’ writing ability is acquired by writing analytical exposition text with the given topic. By using Pearson Product-moment Formula, the researcher assessed the obtained data and analysed by SPSS 23 version for Windows. The data analysis showed the significant value that is considered as a moderate and significant correlation. It could be concluded that there is a significant correlation between twelfth-grade students’ vocabulary mastery and their ability in writing analytical exposition text at SMA Negeri 1 Gianyar in academic year 2021/2022.